Hedging and pricing rent risk with search frictions - CHANG, Briana (Institutional Knowledge at Singapore Management University, 2017)
The desire of risk-averse households to hedge rent risk is thought to increase home ownership and prices. While evidence for the ownership implication is compelling, support for the price effect is mixed. We show that an important reason is search frictions. Rent risk reduces outside options, leading to less-picky buyers and worse home/buyer matches. This attenuates the rise in the price-to-rent ratio that would otherwise occur without frictions. Consistent with our model, a house remains on the market for fewer days when rent risk is higher. Accounting for frictions significantly increases the effect of rent risk on home prices.